Implementasi Sistem Informasi Akuntansi pada BUMDes Lumintu - Yulian Sahri; Toni Nurhadianto; Anggrelia Afrida (Universitas Batanghari, 2022)
This study aims to gain an understanding of the implementation of accounting information system implementation at Lumintu BUMDes, Kepayang Village, Lem debris District, Ogan Komering Ilir Regency. This study uses a qualitative method. Data was collected by means of observation, interviews, and documentation studies. The results of this study indicate that this BUMDes was formed as a means to assist the community in meeting their needs by paying for clean water and savings and loans to the community. With the existence of BUMDes Lumintu Kepayang Village, the community gets convenience from business units in BUMDes, and also BUMDes can provide benefits in public services. The application of an accounting information system in Kepayang Village with the Sedana Dimata application and the PAMS Meter was able to become the main driver of the development of easy-to-use information technology. In this application, it has advantages with data security that is maintained and accurate for business. With the appearance of using modern technology so that it can be used by users and ready to be used anytime.